Postoperative Changes in the Systemic Inflammatory Milieu in Older Surgical Patients. (May 2018) - Shih, Lauren; Guler, Nil; Syed, Daneyal; Hopkinson, William; McComas, Kyra N.; Walborn, Amanda; Hoppensteadt, Debra; Fareed, Jawed; Rondina, Matthew T.
Dysregulated inflammation is a central component of wound healing following surgery. We prospectively enrolled older patients (n = 25, age 65 ± 7 years) undergoing elective total knee arthroplasty or total hip arthroplasty secondary to advanced osteoarthritis (OA) and healthy controls (n = 48). Inflammatory, proangiogenic (vascular endothelial growth factor [VEGF], monocyte chemoattractant protein-1 [MCP-1], and interleukin-8 [IL-8]), and antiangiogenic (interferon γ [IFN-γ] and IL-4) factors were measured using a high-sensitivity biochip. Patients with OA had significantly higher baseline VEGF (10.5 ± 1.2 pg/mL vs 4.8 ± 0.2 pg/mL, P < .001), MCP-1 (130.6 ± 7.7 pg/mL vs 88.6 ± 3.9 pg/mL, P < .0001), and IL-8 (4.0 ± 0.5 pg/mL vs 2.6 ± 0.1 pg/mL, P < .05). Postoperatively, the levels of VEGF (10.5 ± 1.2 pg/mL vs 18.8 ± 1.5 pg/mL, P < .001) and MCP-1 (130.6 ± 7.7 pg/mL vs 153.1 ± 11.5 pg/mL, P < .05) increased significantly. Baseline and postoperative MCP-1 levels correlated positively and significantly with age. The levels of IFN-γ and IL-4 (which has anti-inflammatory properties) did not significantly differ at baseline in patients with OA compared to controls and did not significantly rise postoperatively. We conclude that systemic levels of pro-inflammatory and angiogenic proteins are increased in patients with OA and rise further postoperatively, while proteins that restrain inflammation and angiogenesis do not coordinately rise. These findings implicate imbalance in inflammatory pathways in OA that may contribute to its pathobiology.